Efektifitas Pelaksanaan Fungsi Manajemen dalam Meningkatkan Pelayanan pada BAPPELITBANGDA Kabupaten Tojo Una-Una - Abdul Khalid Hs. Pandipa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims at the Effectiveness of the Implementation of Management Functions in Improving Services at BAPPELITBANGDA Tojo Una-Una Regency. The research location is BAPPELITBANGDA, Tojo Una-Una Regency. The research implementation time was carried out for 3 (three) months, where the researcher compiled a schedule of activities and a predetermined time allocation for each activity. The data analysis technique used in this study is a qualitative descriptive data analysis technique, which is to explain in detail the research studies related to the formulation of the research problem regarding the Effectiveness of Implementation of Management Functions in Improving Services at BAPPELITBANGDA Tojo Una-Una Regency. The results of the research in the form of development and governance are carried out with the aim of creating a prosperous, healthy, harmonious and independent society with the hope that future conditions in Tojo Una-Una Regency, especially at BAPPELITBANGDA, will be in optimal service conditions supported by environmental conditions and excellent quality service. Therefore, a community-based service management system is needed. The implementation of management functions at BAPPELITBANGDA Tojo Una-Una Regency starts from planning BAPPELITBANGDA before carrying out an activity or program starting with planning, so that the planning function runs effectively, mobilizing One of the mobilizations carried out by the Head of BAPPELITBANGDA is to give awards to staff who successfully carry out their duties , the award is in the form of incentives or praise, and supervision carried out by the Head of BAPPELITBANGDA Tojo Una-Una Regency is carried out regularly every month and to each staff in carrying out their work.